Four-dimensional Model for Doctoral Student Support - Simone C Conceição; Lilian H. Hill (Adult Education Research Conference, 2019)
Doctoral education demands significant time, energy, financial, and emotional commitments. Depending on the characteristics of the doctoral student, barriers to completion and challenges with the doctoral process can require unique types of support. The purpose of this paper is to examine institutional and instructional support that lead to doctoral student progress and propose a model involving social, emotional, mental, and behavioral dimensions that derive strategies for doctoral student support.
Keywords: institutional support; instructional support; doctoral process; degree completion